Epidemiology and management of aortic disease: aortic aneurysms and acute aortic syndromes - Bossone, Eduardo; Eagle, Kim A (Nature reviews cardiology, 2021)
The aorta is the 'greatest artery', through which oxygenated blood is delivered from the left ventricle to end organs with each cardiac cycle (200 million litres of blood transported in an average lifetime). The aorta can be affected by a wide spectrum of acute factors (such as cocaine use, weight lifting and trauma) and chronic acquired and/or genetic conditions (such as systemic arterial hypertension and phaeochromocytoma), which variously lead to increased aortic wall stress. The medial layer of the aorta can also be subject to abnormalities (such as Marfan syndrome, bicuspid aortic valve, inflammatory vasculitis, atherosclerosis and infections). Despite important advances in diagnostic and therapeutic interventions, data derived from registries and population-based studies highlight that the burden of aortic diseases remains high. Therefore, specific resources need to be allocated to design and implement preventive strategies (healthy lifestyles, modifications to cardiovascular risk factors, and educational and screening programmes) at individual and community levels. In this Review, we discuss the epidemiology, management and outcomes of the most common aortic diseases, namely, aortic aneurysms and acute aortic syndromes.